Procedura wzorcowania przyrządów pomiarowych na 50 m komparatorze interferencyjnym Głównego Urzędu Miar = Procedure of calibration of measuring instruments using a 50-meter interference comparator at the Central Office of Measures - Wiśniewski, Mariusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The 50 m interference comparator at GUM enables calibration of steel tapes, interferometers, EDMs, total stations and laser trackers. An analysis of mechanical, environmental and line detection factors influencing measurement uncertainty is presented. A procedure for calibrating geodetic total stations has been prepared. Tests of a multicolor laser ADM were performed as part of the EMPIR 20IND02 DynaMITE project.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne